Past, Present and Future of Respiratory Research: A Survey of Canadian Health Care Professionals - Mika Laura Nonoyama; Sunita Mathur; Rosemary Herbert; Heather Jenkins; Michelle Lobchuk; Michelle McEvoy (Canadian Respiratory Journal)
BACKGROUND: The Canadian Respiratory Health Professionals (CRHP) is the multidisciplinary health care professional group of the Canadian Lung Association. Although the CRHP has a growing number of highly qualified researchers, the landscape of their research in Canada has not been described.